2013
DOI: 10.1186/2193-1801-2-362
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of leptospira isolates from animals and humans: phylogenetic analysis identifies the prevalence of intermediate species in India

Abstract: In this study, 191 culture isolates were recovered from suspected samples of animals and humans in Ellinghausen McCullough Johnson and Harris (EMJH) medium and assessed for its morphological features by dark field microscopy. Extracted DNA from individual culture was subjected to different PCR assays for identification and characterization of leptospira. Out of 99 positive leptospira cultures, 52 pathogenic leptospira isolates were characterized at species level by using partial RNA polymerase β-subunit (rpoB)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
50
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 27 publications
3
50
1
Order By: Relevance
“…The major reactive serovars in these regions were Australis, Hardjo, Hebdomadis, Bankinang, Icterohaemorrhagiae, Kaup, Shermani, etc., The reactive Leptospira intermediate species serovars namely Kaup, Tarassovi, Hurstbridge, Shermani may of significance as the prevalence of intermediate species in India has been reported (Balamurugan et al, 2013a;. Hence, further systematic random screening of the samples will determine the exact prevalence of serovars, in this region, which will enable to select the required or prevalent limited panel of serovars representing their respective serogroups to be used for MAT without false negative in the diagnostic laboratory for providing early diagnosis of leptospirosis in humans as well as in animals and prompt treatment to be taken to reduce the extent of problem caused by the leptospira and the economic losses associated with it.…”
Section: Advances In Animal and Veterinary Sciences May 2016 | Volumementioning
confidence: 99%
“…The major reactive serovars in these regions were Australis, Hardjo, Hebdomadis, Bankinang, Icterohaemorrhagiae, Kaup, Shermani, etc., The reactive Leptospira intermediate species serovars namely Kaup, Tarassovi, Hurstbridge, Shermani may of significance as the prevalence of intermediate species in India has been reported (Balamurugan et al, 2013a;. Hence, further systematic random screening of the samples will determine the exact prevalence of serovars, in this region, which will enable to select the required or prevalent limited panel of serovars representing their respective serogroups to be used for MAT without false negative in the diagnostic laboratory for providing early diagnosis of leptospirosis in humans as well as in animals and prompt treatment to be taken to reduce the extent of problem caused by the leptospira and the economic losses associated with it.…”
Section: Advances In Animal and Veterinary Sciences May 2016 | Volumementioning
confidence: 99%
“…Prevalence of leptospiral serovars varies depending on particular geographical regions (4). Titres of various serovars have been reported in horses, but Icterohaemorrhagiae, Bratislava, Copenhageni, and Pomona are among the most prevalent serovars (27).…”
Section: Discussionmentioning
confidence: 99%
“…The intermediate L. wolffii was originally isolated from the urine of a male patient with suspected leptospirosis from Nakornrachasima province, Thailand (13). Some studies have shown that L. wolffii can be detected in clinical samples from human patients with suspected leptospirosis and various kinds of animals in Iran (14) and India (15). The circulation of L. wolffii among different host species is suggestive of its role in the transmission cycle and its potential to cause the disease in human and animal hosts: possibly either symptomatic or asymptomatic diseases.…”
Section: Discussionmentioning
confidence: 99%